PENERAPAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN TAJWID DI SEKOLAH DASAR - Shushmittha Riyazati; Soraya, Irma; Hamdani , A. Saepul (Universitas Islam Malang, 2024)
This research aims to analyze the suitability of the implementation of the discovery learning model with recitation learning, identify supporting factors for the suitability of this model, and explain the challenges that may be faced in its implementation. The research method used is a qualitative research method with a case study at SDIT Hadlanah Darussalam Gontor. related to the discovery learning model, recitation learning curriculum, and its implementation in the learning process. The analysis was carried out by reviewing aspects of the suitability of the discovery learning model with the objectives of the recitation learning curriculum, supporting factors, and challenges that might be faced in its implementation. The research results show that the discovery learning model is in accordance with the Tajwid learning curriculum which emphasizes understanding concepts, applying concepts, developing high-level thinking skills, learning independence, and active learning. Supporting factors such as the characteristics of recitation science, availability of learning resources, educator readiness, student motivation, and a conducive learning environment contribute to the successful implementation of this model. However, there are challenges such as the level of difficulty in discovering concepts, the time required, the varying abilities of students, the availability of resources, and the assessment of learning outcomes that need to be considered. Implementation of the discovery learning model in recitation learning can be carried out optimally through proper planning and management by educators as well as support from schools or educational institutions.